2021
DOI: 10.1111/codi.16005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the implementation of the sigmoid take‐off landmark in the Netherlands

Abstract: Aim:The sigmoid take-off (STO), the point on imaging where the sigmoid sweeps ventral from the sacrum, was chosen as the definition of the rectum during an international Delphi consensus meeting and has been incorporated into the Dutch guidelines since October 2019. The aim of this study was to evaluate the implementation of this landmark 1 year after the guideline implementation and to perform a quality assessment of the STO training.Method: Dutch radiologists, surgeons, surgical residents, interns, PhD stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The Dutch Snapshot Research group recently performed a study in which a large group of 86 multidisciplinary participants (including radiologists, surgeons, and residents) from 45 hospitals in the Netherlands were asked to apply the STO for tumor localization on MRI in 20 cases before and after having received a dedicated training. Overall agreement with an expert-reference improved from 53% before training to 71% after the training (20). These results confirm that training and teaching have a positive effect when applying the STO as a landmark for the localization of rectal and sigmoid tumors on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch Snapshot Research group recently performed a study in which a large group of 86 multidisciplinary participants (including radiologists, surgeons, and residents) from 45 hospitals in the Netherlands were asked to apply the STO for tumor localization on MRI in 20 cases before and after having received a dedicated training. Overall agreement with an expert-reference improved from 53% before training to 71% after the training (20). These results confirm that training and teaching have a positive effect when applying the STO as a landmark for the localization of rectal and sigmoid tumors on imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Hazen et al had 86 experts classify 20 rectal tumors below or above the sigmoid takeoff and found a high positive predictive value, and that training improved the agreement from 53% to 70%. That study used a various group of experts including radiologist, interns, PhD students, surgeons, and physician assistants, and not everyone was used to assess the sigmoid takeoff as a standard imaging landmark, which may have caused the low agreement (70%) [ 13 ]. Other studies have also found a high agreement in validating the sigmoid takeoff between experienced radiologists [ 2 , 14 ], and a study comparing CT scan with MRI images found no significant difference in the sigmoid takeoff [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients, at least 18 years of age, with histopathologically confirmed, (deemed) resectable hr-LARC, with the low border of the tumour at or below the sigmoidal take-off as established on MRI, with a World Health Organization (WHO) performance status of ≤ 1, and fit for (modified dose) triplet chemotherapy are eligible for inclusion [ 59 , 60 ]. An expected gross incomplete resection with overt tumour remaining in the patient after resection, tumour invasion in the neuroforamina, encasement of the ischiadic nerve and invasion of the cortex from S2 upwards are considered unresectable.…”
Section: Methodsmentioning
confidence: 99%